Facile Synthesis of Polysubstituted Indolizines via One‐Pot Reaction of 1‐Acetylaryl 2‐Formylpyrroles and Enals. Issue 3 (27th December 2019) - Gong, Minghua; Guo, Jingcheng; Jiang, Pengrui; Zhang, Ye; Fu, Zhenqian; Huang, Wei
Abstract: An efficient method for the synthesis of polysubstituted indolizines has been developed based on formal [4+2] annulation of 1‐acetylaryl 2‐formylpyrroles with enals, followed by oxidative aromatization. Pyridine‐type six‐membered rings were constructed in this transformation. This transition metal‐free reaction features mild reaction conditions, a broad substrate scope, and excellent functional group tolerance. Notably, the formyl group is well tolerated under reaction conditions. Abstract : An efficient method for the synthesis of polysubstituted indolizines is reported based on formal [4+2] annulation of 1‐acetylaryl 2‐formylpyrroles with enals, followed by oxidative aromatization. Pyridine‐type six‐membered rings were constructed in this transformation. This transition metal‐free reaction features mild reaction conditions, a broad substrate scope, and excellent functional group tolerance. Notably, the formyl group is well tolerated under reaction conditions.